2019
DOI: 10.1016/j.celrep.2019.10.114
|View full text |Cite
|
Sign up to set email alerts
|

henn-1/HEN1 Promotes Germline Immortality in Caenorhabditis elegans

Abstract: SUMMARY The germline contains an immortal cell lineage that ensures the faithful transmission of genetic and, in some instances, epigenetic information from one generation to the next. Here, we show that in Caenorhabditis elegans, the small RNA 3′-2′-O-methyltransferase henn-1/HEN1 is required for sustained fertility across generations. In the absence of henn-1, animals become progressively less fertile, becoming sterile after ~30 generations at 25°C. Sterility in henn-1 mutants is accompanied by severe defect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 80 publications
(187 reference statements)
4
27
0
Order By: Relevance
“…Finally, we show that ZSP-1 contributes to germline immortality. Multiple proteins involved in endo siRNA and piRNA pathways also contribute to germline immortality (Buckley et al, 2012;Simon et al, 2014;Sakaguchi et al, 2014;Svendsen et al, 2019); thus, the defects in germline immortality we see in zsp-1(À) animals are likely connected to the role of ZSP-1 in endo siRNA or piRNA biology. Together, the data lead us to propose that one biological function of the Z granule is to orchestrate and coordinate small RNA-based gene regulation in the germline to ensure the immortal state of the germline.…”
Section: Discussionmentioning
confidence: 95%
“…Finally, we show that ZSP-1 contributes to germline immortality. Multiple proteins involved in endo siRNA and piRNA pathways also contribute to germline immortality (Buckley et al, 2012;Simon et al, 2014;Sakaguchi et al, 2014;Svendsen et al, 2019); thus, the defects in germline immortality we see in zsp-1(À) animals are likely connected to the role of ZSP-1 in endo siRNA or piRNA biology. Together, the data lead us to propose that one biological function of the Z granule is to orchestrate and coordinate small RNA-based gene regulation in the germline to ensure the immortal state of the germline.…”
Section: Discussionmentioning
confidence: 95%
“…It is challenging to compare levels of wild-type piRNAs with those in henn-1 mutants because 2′-O-methylation inhibits 3′ adaptor ligation during high-throughput sequencing library preparation as described ( Munafó and Robb, 2010 ; Svendsen et al, 2019 ). To minimize such a bias, we attempted to clone 2′-O-methyl RNA species by adding polyethylene glycol during the adaptor ligation step as described ( Dard-Dascot et al, 2018 ; Munafó and Robb, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…Because HENN-1 is required for piRNA accumulation in embryos ( Billi et al, 2012 ; Montgomery et al, 2012 ; Svendsen et al, 2019 ), we next profiled small RNAs from wild-type and mutant early embryos. When analyzing the reads mapping piRNA loci, we found that the abundance of piRNAs in henn-1 and parn-1 mutant embryos was reduced to 87.5% and 60.9%, respectively, as compared to that of the wild type ( Figure S1I ).…”
Section: Resultsmentioning
confidence: 99%
“…Reads per million were plotted along the WS258 genome using Integrative Genomics Viewer 2.3.68 ( Robinson et al, 2011 ). ERGO-1 target genes were defined using our ergo-1 libraries, and mutator target genes, piRNA target genes, RDE-1 target genes, and CSR-1 target genes were previously described ( Gu et al, 2009 ; Lee et al, 2012 ; Phillips et al, 2014 ; Svendsen et al, 2019 ; Tsai et al, 2015 ; Zhang et al, 2011 ). Sequencing data is summarized in Table S2 .…”
Section: Methodsmentioning
confidence: 99%